Synchronization of Spatial Planning Policies and Activities with Agriculture in Achieving National Food Self-Sufficiency in Karawang Regen (International Forum of Researchers and Lecturers, 2025)
Karawang Regency, known as one of Indonesia's national rice granaries, significantly contributes to food production in West Java, with a target of 1.5 million tons annually. However, this goal faces challenges due to the loss of 954 hectares of rice fields each year, mainly due to land conversion for industrial and settlement purposes. These issues highlight a lack of synchronization between spatial planning and agricultural policies in Karawang Regency, which forms the basis for this research. The study aims to assess the alignment between spatial planning and agricultural policies to support food self-sufficiency in Karawang Regency. A qualitative research method was used, focusing on policy documents and activities from 2019-2024, supplemented by interviews with relevant stakeholders. The findings suggest that policies are relatively synchronized, although food self-sufficiency is not explicitly mentioned in the 2019-2025 period. Furthermore, activities between spatial planning and agriculture align fairly well in supporting national food self-sufficiency. Recommendations include enhancing the harmonization of medium-term programs across government levels, providing flexibility in budgeting, and clarifying the use of food self-sufficiency terminology. The study also suggests further research on post-harvest handling and improving coordination between farmer groups and post-harvest value-added activities.